Pengaruh Kepemimpinan Autentik terhadap Kedisiplinan Guru SMKN 1 Gunungsari - Rif'atin Hubbaya; Lalu Kiagus Hartawan (PALAPA, 2022)
The purpose of this study was to determine the effect of authentic leadership on teacher discipline at SMKN 1 Gunungsari, West Nusa Tenggara. This research is motivated by the recapitulation of teacher attendance data at SMKN 1 Gunungsari in the even semester of 2022 which shows the arrival of teachers in the first hour on time in carrying out tasks in learning activities is still quite low although several previous studies indicate that authentic leadership can affect employee discipline. A quantitative approach using survey methods is used in this study, where the research population is all teachers of SMKN 1 Gunungsari with a sample of 30 teachers. The data collection technique uses a questionnaire . The t test used as a data analysis technique with the help of the IBM SPSS Statistic 26 program. The results show that t count > t table which is 6.497 > 2.048 and the significance probability is smaller than alpha (0.05) so that concluded that authentic leadership has a significant effect on teacher discipline at SMKN 1 Gunungsari. One way to improve teacher discipline is to increase teacher loyalty and commitment which can be achieved by making the authentic leadership of a school principal effective.